1993
DOI: 10.1029/92ja02263
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous aspects of magnetosheath flow and of the shape and oscillations of the magnetopause during an interval of strongly northward interplanetary magnetic field

Abstract: On February 15, 1978, the orientation of the interplanetary magnetic field (IMF) remained steadily northward for more than 12 hours. The ISEE 1 and 2 spacecraft were located near apogee on the dawnside flank of the magnetotail. IMP 8 was almost symmetrically located in the magnetosheath on the dusk flank and IMP 7 was upstream in the solar wind. Using plasma and magnetic field data, we show that (1) the magnetosheath flow speed on the flanks of the magnetotail steadily exceeded the solar wind speed by 20%, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 35 publications
13
123
4
Order By: Relevance
“…The amplitude of KHI waves at Earth is reported to be in the range of 30-50 nT (ref. 20), whereas amplitudes at Mercury are in excess of 40 nT (refs 8,11). Mercury is also more dynamic, with the KHI characteristic timescales in the range of seconds 8 compared with minutes at Earth.…”
Section: Messenger Spacecraft Observations Of the Khi At Mercurymentioning
confidence: 99%
“…The amplitude of KHI waves at Earth is reported to be in the range of 30-50 nT (ref. 20), whereas amplitudes at Mercury are in excess of 40 nT (refs 8,11). Mercury is also more dynamic, with the KHI characteristic timescales in the range of seconds 8 compared with minutes at Earth.…”
Section: Messenger Spacecraft Observations Of the Khi At Mercurymentioning
confidence: 99%
“…next paragraph), and their intermittent observation may be due to small-scale changes in the distance from the magnetopause to the spacecraft not accounted for in the MHD simulation. The reader is referred to Lavraud and Borovsky [2008] for aspects related to enhanced flows and associated magnetopause wave activity during low M A (see also Chen et al [1993], Lavraud et al [2009] and Taylor et al [2012]). However, this topic is beyond the focus of the present study.…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%
“…The flows along the flanks for a north-south IMF are, by contrast, much larger and have even been shown to exceed the solar wind speed itself by up to 60% in several cases [Lavraud et al, 2007;Rosenqvist et al, 2007]. Utilizing global magnetohydrodynamic (MHD) simulations, Chen et al [1993] and Lavraud et al [2007] have shown that it is indeed possible to attain magnetosheath speeds that exceed that of the solar wind thanks to increased magnetic forces in low b plasma. The process is akin to a slingshot-type effect.…”
Section: Introductionmentioning
confidence: 99%
“…Farther away in the nightside, using data from ISEE1 and 2, IMP 8 and IMP 7, it was found that the magnetotail ceased to flare during a 12 h northward IMF to an anti-sunward distance of 15 R E (Chen et al, 1993). As shown in our Fig.…”
Section: Impact Of Solar Wind Depression On Large Scale Structures: Tmentioning
confidence: 66%